Involvement of Fibroblast Growth Factor Receptor Genes in Benign Prostate Hyperplasia in a Korean Population - Park, Hae Jeong; Kim, Su Kang; Kim, Jong Woo; Lee, Sang Hyub; Yoo, Koo Han; Chung, Joo-Ho (Disease Markers, 2013)
Fibroblast growth factors (FGFs) and their receptors (FGFRs) have been implicated in prostate growth and are overexpressed in benign prostatic hyperplasia (BPH). In this study, we investigated whether single nucleotide polymorphisms (SNPs) of the FGFR genes (FGFR1 and FGFR2) were associated with BPH and its clinical phenotypes in a population of Korean men. We genotyped four SNPs in the exons of FGFR1 and FGFR2 (rs13317 in FGFR1; rs755793, rs1047100, and rs3135831 in FGFR2) using direct sequencing in 218 BPH patients and 213 control subjects. No SNPs of FGFR1 or FGFR2 genes were associated with BPH. However, analysis according to clinical phenotypes showed that rs1047100 of FGFR2 was associated with prostate volume in BPH in the dominant model (GA/AA versus GG, P = 0.010). In addition, a significant association was observed between rs13317 of FGFR1 and international prostate symptom score (IPSS) in the additive (TC versus CC versus TT, P = 0.0022) and dominant models (TC/CC versus TT, P = 0.005). Allele frequency analysis also showed significant association between rs13317 and IPSS (P = 0.005). These results suggested that FGFR genes could be related to progression of BPH.